Genome-wide promoter binding profiling of protein phosphatase-1 and its major nuclear targeting subunits. Issue 12 (18th May 2015) - Verheyen, Toon; Görnemann, Janina; Verbinnen, Iris; Boens, Shannah; Beullens, Monique; Van Eynde, Aleyde; Bollen, Mathieu
Abstract: Protein phosphatase-1 (PP1) is a key regulator of transcription and is targeted to promoter regions via associated proteins. However, the chromatin binding sites of PP1 have never been studied in a systematic and genome-wide manner. Methylation-based DamID profiling in HeLa cells has enabled us to map hundreds of promoter binding sites of PP1 and three of its major nuclear interactors, i.e. RepoMan, NIPP1 and PNUTS. Our data reveal that the α, β and γ isoforms of PP1 largely bind to distinct subsets of promoters and can also be differentiated by their promoter binding pattern. PP1β emerged as the major promoter-associated isoform and shows an overlapping binding profile with PNUTS at dozens of active promoters. Surprisingly, most promoter binding sites of PP1 are not shared with RepoMan, NIPP1 or PNUTS, hinting at the existence of additional, largely unidentified chromatin-targeting subunits. We also found that PP1 is not required for the global chromatin targeting of RepoMan, NIPP1 and PNUTS, but alters the promoter binding specificity of NIPP1. Our data disclose an unexpected specificity and complexity in the promoter binding of PP1 isoforms and their chromatin-targeting subunits.